2007
DOI: 10.1167/iovs.06-1171
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Bevacizumab through the Retina after Intravitreal Injection in the Monkey

Abstract: The results clearly show that the bevacizumab molecule can penetrate the retina and is also transported into the retinal pigment epithelium, the choroid and, in particular, into photoreceptor outer segments after intravitreal injection of Avastin. Active transport mechanisms seem to be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
155
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(177 citation statements)
references
References 23 publications
16
155
0
6
Order By: Relevance
“…Accordingly, ranibizumab was developed as a cleaved Fab lacking an Fc region as the smaller size was thought to enhance its diffusion from the vitreous into the retina and choroid (Ferrara et al 2006). Contrary to this original hypothesis, immunohistochemistry studies and findings of systemic VEGF blockade after intravitreal injection of bevacizumab proved the effective penetration of the larger molecule through all retinal layers and the choroid, despite its bigger molecule size (Heiduschka et al 2007). The ease of penetrating the retina and passing into the systemic blood circulation across the blood-retina barrier is thought to be mediated by the presence of FcRn receptors (Kim et al 2009).…”
Section: Discussionmentioning
confidence: 78%
“…Accordingly, ranibizumab was developed as a cleaved Fab lacking an Fc region as the smaller size was thought to enhance its diffusion from the vitreous into the retina and choroid (Ferrara et al 2006). Contrary to this original hypothesis, immunohistochemistry studies and findings of systemic VEGF blockade after intravitreal injection of bevacizumab proved the effective penetration of the larger molecule through all retinal layers and the choroid, despite its bigger molecule size (Heiduschka et al 2007). The ease of penetrating the retina and passing into the systemic blood circulation across the blood-retina barrier is thought to be mediated by the presence of FcRn receptors (Kim et al 2009).…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][22][23][24]28,30,32,33,[41][42][43] Bevacizumab is a recombinant humanized full-length monoclonal antibody of VEGF that penetrates the retina and is transported into the photoreceptor outer segments, RPE, and choroid after intravitreal injection. 44 The half-life of bevacizumab in the vitreous is 5.6 days, and it remains in the eye for 4 to 6 weeks. 45 Many studies of other macular diseases have reported that the CMT starts decreasing or stabilizes in most eyes at 3-6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be attributable to the findings that both full-length antibody (bevacizumab) and Fab fragment (ranibizumab) drugs are able to penetrate into all retinal layers, reach the choroid, and accumulate in the wall of the choroidal vessel (26)(27)(28) . As VEGF functions by inducing vessel dilation and increasing ocular blood flow, which is mediated by increased nitric oxide production (29) , VEGF inhibition by these drugs may cause constriction of the choroidal vessels.…”
Section: Discussionmentioning
confidence: 99%